Neuromodulatory effects of transcranial magnetic stimulation on language performance in healthy participants: Systematic review and meta-analysis - Qu, Xingfang; Wang, Zichao; Cheng, Yao; Xue, Qingwei; Li, Zimu; Li, Lu; Feng, Liping; Hartwigsen, Gesa; Chen, Luyao (Frontiers in Human Neuroscience, 2022)
Background: The causal relationships between neural substrates and human language have been investigated by transcranial magnetic stimulation (TMS). However, the robustness of TMS neuromodulatory effects is still largely unspecified. This study aims to systematically examine the efficacy of TMS on healthy participants' language performance. Methods: For this meta-analysis, we searched PubMed, Web of Science, PsycINFO, Scopus, and Google Scholar from database inception until October 15th, 2022 for eligible TMS studies on language comprehension and production in healthy adults published in English. The quality of the included studies was assessed with the Cochrane risk of bias tool. Potential publication biases were assessed by funnel plots and the Egger Test. We conducted overall as well as moderator meta-analyses. Effect sizes were estimated using Hedges'g (g) and entered into a three-level random effects model. Results: Thirty-seven studies (797 participants) with 77 effect sizes were included. The three-level random effects model revealed significant overall TMS effects on language performance in healthy participants (RT: g = 0.16, 95% CI: 0.04-0.29; ACC: g = 0.14, 95% CI: 0.04-0.24). Further moderator analyses indicated that (a) for language tasks, TMS induced significant neuromodulatory effects on semantic and phonological tasks, but didn't show significance for syntactic tasks; (b) for cortical targets, TMS effects were not significant in left frontal, temporal or parietal regions, but were marginally significant in the inferior frontal gyrus in a finer-scale analysis; (c) for stimulation parameters, stimulation sites extracted from previous studies, rTMS, and intensities calibrated to the individual resting motor threshold are more prone to induce robust TMS effects. As for stimulation frequencies and timing, both high and low frequencies, online and offline stimulation elicited significant effects; (d) for experimental designs, studies adopting sham TMS or no TMS as the control condition and within-subject design obtained more significant effects. Discussion: Overall, the results show that TMS may robustly modulate healthy adults' language performance and scrutinize the brain-and-language relation in a profound fashion. However, due to limited sample size and constraints in the current meta-analysis approach, analyses at a more comprehensive level were not conducted and results need to be confirmed by future studies.